2014
DOI: 10.1371/journal.pone.0103311
|View full text |Cite
|
Sign up to set email alerts
|

An Abp1-Dependent Route of Endocytosis Functions when the Classical Endocytic Pathway in Yeast Is Inhibited

Abstract: Clathrin-mediated endocytosis (CME) is a well characterized pathway in both yeast and mammalian cells. An increasing number of alternative endocytic pathways have now been described in mammalian cells that can be both clathrin, actin, and Arf6- dependent or independent. In yeast, a single clathrin-mediated pathway has been characterized in detail. However, disruption of this pathway in many mutant strains indicates that other uptake pathways might exist, at least for bulk lipid and fluid internalization. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…As shown ( Figure S4 ), eisosomal size and organization appear to be the same in both strains, indicating the long invaginations are not due to eisosomal defects. Given that a bimodal distribution of invaginations was observed in the RR-EE-expressing cells, it is possible that the long invaginations represent activation of alternative endocytic pathways [ 31, 32 ]. However, even if these longer invaginations (≥200 nm) are excluded from calculations, there is still a significant increase in invagination length in the RR-EE mutants (75 nm compared to 61 nm in wild-type p ≥ 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…As shown ( Figure S4 ), eisosomal size and organization appear to be the same in both strains, indicating the long invaginations are not due to eisosomal defects. Given that a bimodal distribution of invaginations was observed in the RR-EE-expressing cells, it is possible that the long invaginations represent activation of alternative endocytic pathways [ 31, 32 ]. However, even if these longer invaginations (≥200 nm) are excluded from calculations, there is still a significant increase in invagination length in the RR-EE mutants (75 nm compared to 61 nm in wild-type p ≥ 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, all three shared functions of Abp1 depend on its SH3 domain, but only two of these (shared with Sla2 and Sac6 ) depend on its ability to bind F-actin ( Quintero-Monzon et al 2005 ). Recently, Abp1 was found to be essential for an alternative endocytic pathway in yeast, perhaps related to its synthetic lethality with factors central to the conventional CME pathway ( Aghamohammadzadeh et al 2014 ). While purified Abp1 alone shows no effects on actin-filament dynamics or organization in vitro ( Goode et al 2001 ; Quintero-Monzon et al 2005 ), when bound to its ligand Aim3 it can cap actin-filament barbed ends ( Michelot et al 2013 ).…”
Section: Mechanisms Of Actin Assembly and Turnovermentioning
confidence: 99%
“…Prk1 was first discovered as a spontaneous suppressor of a pan1 allele, and Ark1 was identified as a binding partner of Sla2 ( Cope et al 1999 ; Zeng and Cai 1999 ). The Ark1 and Prk1 kinases appear to be largely redundant in their functions, although there is evidence that they also fulfill some unique roles ( Cope et al 1999 ; Watson et al 2001 ; Aghamohammadzadeh et al 2014 ). A third related protein kinase, Akl1 , is much less well studied.…”
Section: Vesicle Scission and Uncoatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite genetic evidence that additional endocytic routes existed ( Chu et al, 1996 ; Payne et al, 1988 ), yeast were thought to rely solely on CME; however, recent evidence demonstrated the existence of a yeast CIE pathway that depends on the GTPase Rho1 and the formin Bni1 ( Prosser and Wendland, 2012 ; Prosser et al, 2011 ). In addition, a CIE pathway was discovered in Candida albicans ( Epp et al, 2013 ) and an alternative endocytic route in S. cerevisiae , using only a few CME proteins, might function when CME is impaired ( Aghamohammadzadeh et al, 2014 ). Thus, yeasts use multiple internalization pathways, but the mechanisms of cargo selection and sorting, as well as regulation of these ‘alternative’ non-CME pathways remain poorly understood in yeast and mammals.…”
Section: Introductionmentioning
confidence: 99%